Autologous stem cell transplantation for follicular lymphoma is of most benefit early in the disease course and can result in durable remissions, irrespective of prior rituximab exposure. (18th January 2014) - Kothari, Jaimal; Peggs, Karl S.; Bird, Antonia; Thomson, Kirsty J.; Morris, Emma; Virchis, Andres E.; Lambert, Jonathan; Goldstone, Anthony H.; Linch, David C.; Ardeshna, Kirit M.
Summary The role of autologous stem cell transplantation (ASCT) and the optimal timing of such transplants in patients with follicular lymphoma (FL) remains contentious. We present a single‐centre experience documenting the outcomes of 70 FL patients who underwent BEAM (carmustine, cytarabine, etopside, melphalan)‐conditioned ASCT between 1988 and 2009. With a median follow‐up of 6·8 years (0·1–19·2), the 7‐year overall survival (OS) and progression‐free survival (PFS) from the date of ASCT was 76% and 60%, respectively. A significant difference in OS was found when comparing the patients transplanted in first or second remission versus those transplanted in later remissions (P = 0·02) and this significance was maintained when OS was calculated from the date of diagnosis (P = 0·03). There was a plateau on the PFS curves for patients transplanted in either first or second remissions after 9·3 and 6·4 years respectively, suggesting that these groups may never relapse. No differences were seen in OS or PFS in those treated with rituximab prior to transplant versus those who were not. Our data shows that BEAM ASCT can be a highly effective treatment in patients with FL early in the disease course, and that a proportion of patients experience prolonged disease‐free survival and may be cured.